Cytochemical localization of lipids in the venom glands of worker bees of Apis mellifera (Hymenoptera, Apidae) - de Abreu, RMM; de Moraes, RLMS; Caetano, F. H.; Camargo-Mathias, M. I. (California State University, 2003)
The technique of osmium imidazol for the ultrastructural detection of lipids in the secretory cells of the venom gland of 14-days old worker bees of Apis mellifera L. demonstrated the presence of these components at various sites of the gland. These lipids were found mainly associated to the external region of the basal lamina and the microvilli, in the intercellular spaces, in the cuticle of the collecting canaliculi and in the secretion contained in the glandular lumen. Therefore, in addition to revealing the presence of lipids in the secretion, this technique also allowed us to attribute an exogenous origin to the lipids in the secretion; they are taken up from the haemolymph.
Keywords: Apis mellifera; venom gland; cytochemical; lipids